Conformations of cyclopentasilane stereoisomers control molecular junction conductance. Issue 9 (13th June 2016) - Li, Haixing; Garner, Marc H.; Shangguan, Zhichun; Zheng, Qianwen; Su, Timothy A.; Neupane, Madhav; Li, Panpan; Velian, Alexandra; Steigerwald, Michael L.; Xiao, Shengxiong; Nuckolls, Colin; Solomon, Gemma C.; et al.
Abstract : Here we examine the impact of ring conformation on the charge transport characteristics of cyclic pentasilane structures bound to gold electrodes in single molecule junctions. Abstract : Here we examine the impact of ring conformation on the charge transport characteristics of cyclic pentasilane structures bound to gold electrodes in single molecule junctions. We investigate the conductance properties of alkylated cyclopentasilane cis and trans stereoisomers substituted in the 1, 3-position with methylthiomethyl electrode binding groups using both the scanning tunneling microscope-based break junction technique and density functional theory based ab initio calculations. In contrast with the linear ones, these cyclic silanes yield lower conductance values; calculations reveal that the constrained dihedral geometries occurring within the ring are suboptimal for σ-orbital delocalization, and therefore, conductance. Theoretical calculations reproduce the measured conductance trends for both cis and trans isomers and find several distinct conformations that are likely to form stable molecular junctions at room temperature. Due to the weakened σ-conjugation in the molecule, through-space interactions are found to contribute significantly to the conductance. This manuscript details the vast conformational flexibility in cyclopentasilanes and the tremendous impact it has on controlling conductance.